Molecular basis of dengue virus serotype 2 morphological switch from 29°C to 37°C. - Xin-Ni Lim; Chao Shan; Jan K Marzinek; Hongping Dong; Thiam Seng Ng; Justin S G Ooi; Guntur Fibriansah; Jiaqi Wang; Chandra S Verma; Peter J Bond; Pei-Yong Shi; Shee-Mei Lok (PLoS Pathogens, 2019)
The ability of DENV2 to display different morphologies (hence different antigenic properties) complicates vaccine and therapeutics development. Previous studies showed most strains of laboratory adapted DENV2 particles changed from smooth to "bumpy" surfaced morphology when the temperature is switched from 29°C at 37°C. Here we identified five envelope (E) protein residues different between two alternative passage history DENV2 NGC strains exhibiting smooth or bumpy surface morphologies. Several mutations performed on the smooth DENV2 infectious clone destabilized the surface, as observed by cryoEM. Molecular dynamics simulations demonstrated how chemically subtle substitution at various positions destabilized dimeric interactions between E proteins. In contrast, three out of four DENV2 clinical isolates showed a smooth surface morphology at 37°C, and only at high fever temperature (40°C) did they become "bumpy". These results imply vaccines should contain particles representing both morphologies. For prophylactic and therapeutic treatments, this study also informs on which types of antibodies should be used at different stages of an infection, i.e., those that bind to monomeric E proteins on the bumpy surface or across multiple E proteins on the smooth surfaced virus.